Internet of Things with 8051 and ESP8266 - Gehlot, Anita 1984-; Singh, Rajesh; Malik, Praveen Kumar 1975-; Gupta, Lovi Raj 196X-; Singh, Bhupendra 199X- (CRC Press, Taylor & Francis Group, 2021)
Internet of Things with 8051 and ESP8266 provides a platform to get started with the Internet of Things (IoT) with 8051. This book describes programming basics and how devices interface within designed systems. It presents a unique combination of 8051 with ESP8266 and I/O devices for IoT applications supported by case studies to provide the solutions to real-time problems. The programs and circuits have been tested on real hardware and explore different areas in IoT applications. Divided into four sections, it explains the customized boards for IoT applications followed by the means by which 8051 and ESP8266 interface with I/O devices. It spans levels from basic to advanced interfacing with special devices, server design, and data logging with different platforms.Features: - Covers how I/O devices interface with 8051 and ESP8266 - Explains the basic concepts of interfacing complexity using applications with examples- Provides hands-on practice exercises with 8051 and ESP8266 for IoT applications - Discusses both case studies and programming tests on real hardware during industrial and student projects - Reviews the integration of smart devices with IoTInternet of Things with 8051 and ESP8266 is intended for senior undergraduate and graduate students in electrical and electronics engineering, but anyone with an interest in the professional curriculum of electrical and electronics engineering will find this book a welcome addition to their collection